Analisis Manajemen Risiko Pada Warung Mbah Lanang Banyuwangi Dengan Pendekatan Kontekstual Deskriptif Menggunakan Metode ISO 31000 - Muhammad Rivaldy Hisham; Wisnu Yuwono (Jurnal Bangkit Indonesia, 2023)
Warung Mbah Lanang Banyuwangi is a small and medium business engaged in the food and beverage sector which also implements a Point Of Sales system in its sales activities. However, WMLB must also consider potential risks such as human error, virus exposure, power outages/internet connection interruptions, data breaches and POS equipment theft in implementing the POS system. Therefore, these risks must be appropriately managed to reduce the negative impact. In this study, risk analysis was carried out using the risk register technique, distribution risk structure, risk response, and risk analysis to identify, assess and handle potential risks in the WMLB POS system. The research results show that human error is the most significant risk, with a probability of 25%. The lowest bet is the theft of POS devices, with a probability value of 5%. Efforts to overcome this risk include intensive training and supervision, periodic data backup, use of a UPS and a guaranteed security system, updating security systems regularly and installing security features on cash register machines.